Efficacy of home based computerized adaptive cognitive training in patients with post stroke cognitive impairment: a randomized controlled trial - Amit Kumar Soni; Mohit Kumar; Saroj Kothari (Scientific Reports)
Abstract Post-stroke cognitive impairment is a common consequence of stroke, characterized by deficits in language, cognitive functioning, functional abilities. Innovative technological approaches, such as computerized cognitive retraining, offer promising strategies for mitigating the cognitive challenges. Despite their potential, the impact of these interventions on neuropsychological function and daily living capabilities has poor outcomes. In this randomized controlled trial (RCT), we assessed the effectiveness of a 4-week, remotely-delivered, multi-domain, computer-adaptive cognitive retraining (CACT) program in patients with post-cognitive cognitive impairment. Fifty male participants were randomly assigned to either the experimental group, which underwent the CACT program tailored to individual performance levels, or an active control group that received standard care. The evaluation focused on neuropsychological functions such as attention, memory, and executive processes, alongside daily living skills. Results indicated that participants in the CACT group exhibited notable improvements in several cognitive areas, including processing speed, category fluency, and visual confrontation naming, when compared to the control group. Nonetheless, enhancements in functional abilities, encompassing basic and instrumental activities of daily living (ADL), were minimal, with no significant changes reported post-intervention. This study demonstrates that CACT effectively improves cognitive functions in patients with post-stroke cognitive impairment during the spontaneous recovery period, suggesting that training patients at their optimal performance levels can lead to meaningful cognitive benefits. These findings are specific to patients recovering from stroke-induced cognitive deficits and highlight the need for further research to generalize these results to other populations with vascular cognitive impairment.